Oxidation of P700 Ensures Robust Photosynthesis - Shimakawa, Ginga; Miyake, Chikahiro (Frontiers in Plant Science, 2018)
In the light, photosynthetic cells can potentially suffer from oxidative damage derived from reactive oxygen species. Nevertheless, a variety of oxygenic photoautotrophs, including cyanobacteria, algae, and plants, manage their photosynthetic systems successfully. In the present article, we review previous research on how these photoautotrophs safely utilize light energy for photosynthesis without photo-oxidative damage to photosystem I (PSI). The reaction center chlorophyll of PSI, P700, is kept in an oxidized state in response to excess light, under high light and low CO2 conditions, to tune the light utilization and dissipate the excess photo-excitation energy in PSI. Oxidation of P700 is co-operatively regulated by a number of molecular mechanisms on both the electron donor and acceptor sides of PSI. The strategies to keep P700 oxidized are diverse among a variety of photoautotrophs, which are evolutionarily optimized for their ecological niche.